2021
DOI: 10.3389/fmars.2021.660798
|View full text |Cite
|
Sign up to set email alerts
|

Leatherback Turtles in the Eastern Gulf of Mexico: Foraging and Migration Behavior During the Autumn and Winter

Abstract: We deployed 19 satellite tags on foraging adult leatherback turtles, including 17 females and 2 males, captured in the northeastern Gulf of Mexico in 2015, 2018, and 2019 in order to study regional distribution and movements. Prior to our study, limited data were available from leatherbacks foraging in the Gulf of Mexico. Tag deployment durations ranged from 63 to 247 days and turtles exhibited three distinct behavior types: foraging, transiting, or rapidly switching between foraging and transiting. Some femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…The results also complement known migratory trajectories such as the loggerheads moving from north to south GoM (Girard et al, 2009;Hart et al, 2012;Tucker et al, 2014;Hart et al, 2018b). The use of deep oceanic zones in the GoM and WC by adult leatherbacks (Dermochelys coriacea) and younger life-stages of the other species during their oceanic dispersal, complements the intense and extended use of the study area (Putman and Mansfield, 2015;Aleksa et al, 2018;Putman et al, 2020;Evans et al, 2021;Sasso et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…The results also complement known migratory trajectories such as the loggerheads moving from north to south GoM (Girard et al, 2009;Hart et al, 2012;Tucker et al, 2014;Hart et al, 2018b). The use of deep oceanic zones in the GoM and WC by adult leatherbacks (Dermochelys coriacea) and younger life-stages of the other species during their oceanic dispersal, complements the intense and extended use of the study area (Putman and Mansfield, 2015;Aleksa et al, 2018;Putman et al, 2020;Evans et al, 2021;Sasso et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…The resultant output encompassed the identified HUAs in Aleksa et al (2018); thus, the inclusion of telemetry data was not necessary for this species. A recently published Leatherback telemetry study confirmed the HUAs identified using the previous telemetry and observer data (Sasso et al 2021). Insufficient data were available on Hawksbill turtles to identify HUAs using these methods.…”
Section: Methodssupporting
confidence: 66%
“…We identified a broad suite of aerial survey, tracking, and observer data that could be used to characterize important areas for sea turtles within the study area. Although we did not include telemetry data for leatherback sea turtles due to timing constraints for acquiring and processing the data, the combined KDEs encompassed the identified HUAs in [38,64]. For ESA-listed sea turtles and giant manta rays, avoiding or minimizing risk from aquaculture activities, particularly risk from entanglement, obstruction of migratory corridors, or alteration of foraging habitat, will be important to their recovery.…”
Section: Discussionmentioning
confidence: 99%